A case of unilateral post-COVID-19 adrenal haemorrhage and follow-up during pregnancies. (21st December 2022) - Mangone, Alessandra; Yousuf, Quratulain; Arlt, Wiebke; Prete, Alessandro; Shaheen, Fozia; Krishnasamy, Senthil-kumar; Elhassan, Yasir S; Ronchi, Cristina L
Abstract : Summary: The spectrum of endocrine-related complications of COVID-19 infection is expanding; one of the most concerning of which is adrenal haemorrhage due to the risk of catastrophic adrenal crisis. In this study, we present a case that highlights the challenging management of a large, indeterminate unilateral adrenal mass during pregnancy and draws attention to a rare yet probably underestimated complication of COVID-19. During hospitalization for severe COVID-19 pneumonia, a 26-year-old woman was incidentally found to have a 12.5 cm heterogeneous left adrenal mass. Soon after the discovery, she became pregnant and upon referral, she was in the seventh week of gestation, without clinical or biochemical features of hormonal excess. The uncertainty of the diagnosis and the risks of malignancy and surgical intervention were discussed with the patient, and a period of radiological surveillance was agreed upon. An MRI scan performed 3 months later showed a size reduction of the adrenal lesion to 7.9 cm, which was against malignancy. A Doppler ultrasound showed a non-vascular, well-defined round lesion consistent with an adrenal haematoma, likely a complication of the recent COVID-19 infection. The multidisciplinary team recommended further radiological follow-up. The patient then spontaneously had miscarriage at 12 weeks gestation. Subsequent radiological surveillance showed a further size reduction of the adrenal lesion to 5.5 cm. The patient conceived again during follow-up, and the repeated Doppler ultrasound showed stable appearances of the adrenal mass, and thus, it was agreed to continue radiological monitoring after delivery. The pregnancy was uneventful, and the patient delivered a healthy baby. An MRI scan performed after delivery showed a stable but persistent lesion consistent with a likely underlying adrenal lesion. Learning points: Unilateral adrenal haemorrhage can occur as a complication of COVID-19 and should be considered in the differential diagnosis of heterogeneous adrenal masses if there is a history of recent infection. Management of large indeterminate adrenal masses during pregnancy poses several challenges and should be led by an experienced multidisciplinary team. Underlying adrenal tumours may trigger non-traumatic haemorrhages, especially if exacerbated by stressful illness.